Penetapan Setandar Warna Daun Sebagai Upaya Identifikasi Status Hara ( N) Tanaman Jagung ( zea mays L ) Pada Tanah Regosol - Wisnu Sapto Nugroho (Fakultas Pertanian UMY, 2014)
A study, entitled "Determination of Leaf Color Standards For Identify the Nitrogen (N) Status of Corn (Zea mays L.) in Regosol Soil", was conducted from February up to August 2013 in the experimental land of Universitas Muhammadiyah Yogyakarta, aims to obtain a standard of leaves green color on the growth of corn as the identification of the status of nitrogen adequacy. The experiment was done using the experimental methods are arranged in a completely randomized design (CRD) which consisted of 7 treatments : 125 kg N/ha (N1), 150 kg N/ha (N2), 175 kg N/ha (N3), 200 kg N/ha (N4), 225 kg N/ha (N5), 250 kg N/ha (N6), and 275 kg N/ha (N7). The result showed that Leaf color scale is can be set on a color between 5GY 5/8 and 5GY 6/8 on the doses between 250 kg N/ha and 275 kg N/ha. Dose of 250 kg N/ha gave the highest of plant height. In the other side, dose of 275 kg N/ha gave the highest results in the components of seed weight/cob and grain weight of 100 seeds at 14% moisture content. Key words: Corn, Nitrogen Status, Leaf Color Standards